Transcriptomic Analysis of the Kuruma Prawn Marsupenaeus japonicus Reveals Possible Peripheral Regulation of the Ovary - Tsutsui, Naoaki; Kobayashi, Yasuhisa; Izumikawa, Kouichi; Sakamoto, Tatsuya (Frontiers in Endocrinology, 2020)
Crustacean reproduction has been hypothesized to be under complex endocrinological regulation by peptide hormones. To further improve our understanding of the mechanisms underlying this complex regulation, knowledge is needed regarding the hormones not only of the central nervous system such as the X-organ/sinus gland (XOSG), brain, and thoracic ganglia, but also the peripheral gonadal tissues. For example, in vertebrates, some gonadal peptide hormones including activin, inhibin, follistatin, and relaxin are known to be involved in the reproductive physiology. Therefore, it is highly likely that some peptide factors from the ovary are serving as the signals among peripheral tissues and central nervous tissues in crustaceans. In this work, we sought to find gonadal peptide hormones and peptide hormone receptors by analyzing the transcriptome of the ovary of the kuruma prawn Marsupenaeus japonicus. The generated ovarian transcriptome data led to the identification of five possible peptide hormones, including bursicon-α and -β, the crustacean hyperglycemic hormone (CHH)-like peptide, insulin-like peptide (ILP), and neuroparsin-like peptide (NPLP). Dominant gene expressions for the bursicons were observed in the thoracic ganglia and the ovary, in the CNS for the CHH-like peptide, in the heart for NPLP, and in the ovary for ILP. Since the gene expressions of CHH-like peptide and NPLP were affected by a CHH (Penaeus japonicus sinus gland peptide-I) from XOSG, we produced recombinant peptides for CHH-like peptide and NPLP using Escherichia coli expression system to examine their possible peripheral regulation. As a result, we found that the recombinant NPLP increased vitellogenin gene expression in incubated ovarian tissue fragments. Moreover, contigs encoding putative receptors for insulin-like androgenic gland factor, insulin, neuroparsin, and neuropeptide Y/F, as well as several contigs encoding orphan G-protein coupled receptors and receptor-type guanylyl cyclases were also identified in the ovarian transcriptome. These results suggest that reproductive physiology in crustaceans is regulated by various gonadal peptide hormones, akin to vertebrates.